PUSAT SENI TARI BANJAR DI BANJARBARU - Lestari, Brigita Puji; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The development of Banjar dance in Banjarbaru is fully supported by dance activists, as proven by the frequent encounters of dance training, dance creation, and performances in several public places. However, inadequate facilities and infrastructure and the lack of regeneration of dancers are threats that can shift the existence of Banjar dance. In an effort to accommodate and preserve Banjar dance in Banjarbaru, it is necessary to design a dance center with the main target of dance activists and the younger generation of Banjarbaru city. Through the concept of manyaru (calling) with a metaphorical architectural approach, the elements, traits, and philosophy of Banjar dance are transformed into architectural aspects, namely circulation, form, to elements in open space so that the Banjar dance center is created which is contemporary and has a distinctive Banjar design image. This is expected to attract the interest and attention of the younger generation and can be a space for activities that are suitable with the characteristics of the millennial generation and Banjarbaru dance activists.